2000
DOI: 10.1097/00006454-200003000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety and immunogenicity of heptavalent pneumococcal conjugate vaccine in children

Abstract: This heptavalent pneumococcal conjugate appears to be highly effective in preventing invasive disease in young children and to have a significant impact on otitis media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
1,127
4
73

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,078 publications
(1,241 citation statements)
references
References 11 publications
28
1,127
4
73
Order By: Relevance
“…Efficacy was assumed being absent before the age of 5 months. Based on the results of Black et al [13], efficacy was assumed to be 85.7% at the ages of 5-11 months and 93.9% at the ages of 12 months to 9 years. Vaccine effectiveness was assumed to decline 3% per year starting 5 years after the last dosage [11].…”
Section: Updating the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficacy was assumed being absent before the age of 5 months. Based on the results of Black et al [13], efficacy was assumed to be 85.7% at the ages of 5-11 months and 93.9% at the ages of 12 months to 9 years. Vaccine effectiveness was assumed to decline 3% per year starting 5 years after the last dosage [11].…”
Section: Updating the Modelmentioning
confidence: 99%
“…In Western Europe, it is estimated that every child experiences one or more episodes of otitis media before the age of 2 years [7,8]. A number of studies have assessed the potential economical impact of mass infant vaccination with PCV7 (Prevnar; Wyeth) [9][10][11][12], since the first published clinical trial showed the high efficacy of this vaccine in the prevention of IPD [13] (see also McIntosh [14] for a recent review). Additionally, ongoing research has provided important new data.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical trials, PCV has proved to be protective for invasive pneumococcal disease caused by vaccine serotypes [12] as well as reducing their carriage [3], and hence a possible herd immunity effect. The observed reduction in vaccine serotypes has also been associated with an increase in carriage of non-vaccine serotypes in vaccinated children in carriage studies [13] and in vaccine trials for PCV against otitis media [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, conjugation of PS to protein carriers allows T cell help through recruitment of carrier-specific T cells [10][11][12][13][14] and makes the PPS immunogenic in early infancy (reviewed in [15]). Protective immunity against both invasive disease [16,17] and otitis media [18] has been demonstrated after vaccination of infants with pneumococcal conjugate vaccines. In addition, pneumococcal conjugate vaccines induce PS-specific memory B cells [19][20][21], similar to what has been observed after immunization with protein antigens.…”
Section: Introductionmentioning
confidence: 99%